Fifth metacarpal neck fractures: fixation with antegrade locked flexible intramedullary nailing - Pogliacomi, Francesco; Mijno, Elisabetta; Pedrazzini, Alesssio; Tocco, Silvio; Tonani, Massimo; Ceccarelli, Francesco; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2017)
Background: Fifth metacarpal neck fractures (commonly named “boxer’s fractures”) are the most common metacarpal injuries and usually affect young active people. These lesions are mainly treated conservatively. Their surgical management, if indicated, is still a matter of debate. Different procedures have been described. The aim of this study was to evaluate the outcomes of 18 boxer’s fractures which were synthesized with antegrade locked flexible intramedullary nailing. Materials and methods: All patients, at a mean follow-up of 45 months, were clinically evaluated using the Disabilities of the Arm, Shoulder and Hand (DASH) score and the Patient Rated Wrist/Hand Evaluation (PRWHE). Active and passive range of motion (ROM) of metacarpo-phalangeal (MP), proximal and distal interphalangeal (PIP and DIP) joints and Total Active Motion (TAM), and grip strength were also analyzed. Apex dorsal angulation and axial shortening were radiologically measured preoperatively and at final follow-up. Results: Clinical and radiological results which were observed were satisfactory. No TAM and grip strength differences were recorded between the operated and healthy contralateral hand. Conclusions: According to the positive outcomes and the low rate of complications of this study, antegrade locked flexible intramedullary nailing can be considered a valid treatment option in boxer’s fractures.